2012
DOI: 10.1103/physrevd.85.045029
|View full text |Cite
|
Sign up to set email alerts
|

Quantum statistics and noncommutative black holes

Abstract: We study the behaviour of a scalar field coupled to a noncommutative black hole which is described by a κ-cylinder Hopf algebra. We introduce a new class of realizations of this algebra which has a smooth limit as the deformation parameter vanishes. The twisted flip operator is independent of the choice of realization within this class. We demonstrate that the R-matrix is quasi-triangular up to the first order in the deformation parameter. Our results indicate how a scalar field might behave in the vicinity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 69 publications
(156 reference statements)
1
47
0
Order By: Relevance
“…Experimental results on exclusive twophoton production of W + W − and + − pairs in γ γ interactions reported by the CMS and ATLAS Collaborations [9][10][11][12] have demonstrated that it is possible to measure such events with the experimental apparatus already available at the LHC, allowing for novel studies of QCD at very high energies and searches for Beyond Standard Model Physics (see, e.g., Ref. [49][50][51][52][53][54][55][56][57][58][59]). This motivates us to revisit the analysis of double vector meson production in ultra peripheral heavy ion collisions performed some time ago in Refs.…”
mentioning
confidence: 99%
“…Experimental results on exclusive twophoton production of W + W − and + − pairs in γ γ interactions reported by the CMS and ATLAS Collaborations [9][10][11][12] have demonstrated that it is possible to measure such events with the experimental apparatus already available at the LHC, allowing for novel studies of QCD at very high energies and searches for Beyond Standard Model Physics (see, e.g., Ref. [49][50][51][52][53][54][55][56][57][58][59]). This motivates us to revisit the analysis of double vector meson production in ultra peripheral heavy ion collisions performed some time ago in Refs.…”
mentioning
confidence: 99%
“…The fermionic vacuum correction and its influence has also been investigated in earlier works [91][92][93][94]. In a recent work [95], we generalized the proper accounting of renormalized fermionic vacuum fluctuation in the two flavour PQM model to the non-zero chemical potentials and found that the position of CEP shifts to a significantly higher chemical potential in the µ and T plane of the phase diagram, due to the influence of fermionic vacuum term in our PQMVT (PQM model with vacuum term) model calculations. Very recently, Schaefer et.…”
mentioning
confidence: 95%
“…However, in the casex µ given by (2.44), e iq µ x a ϕaµ(∂) 1 = e ipx and (A.7) reduces to 8) which leads to the following quantized plane waves…”
Section: Jhep07(2017)116mentioning
confidence: 99%
“…From [43], one concludes in particular that (4.3) and (4.4) do not have (perturbative) UV/IR mixing. Indeed, a standard analysis as in e.g [43] shows that the quadratic part of the effective action for (4.3) (i.e 2-point function part) receives 2 types of one-loop contributions whose typical form is given by 6) whereφ is the Fourier transform of φ, in which 8) up to unessential overall factors. For θ = 0, one can check that ω I is finite (even for m = 0) while one obtains ω II (0, k 2 ) ∼ δ(k 2 )ω I (with similar expression for ω II (k 1 , 0)).…”
Section: Jhep07(2017)116mentioning
confidence: 99%
See 1 more Smart Citation